2022
DOI: 10.1111/jedm.12349
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐Group Joint Modeling of Item Responses, Response Times, and Action Counts with the Conway‐Maxwell‐Poisson Distribution

Abstract: Multiple group modeling is one of the methods to address the measurement noninvariance issue. Traditional studies on multiple group modeling have mainly focused on item responses. In computer-based assessments, joint modeling of response times and action counts with item responses helps estimate the latent speed and action levels in addition to latent ability. These two new data sources can also be used to further address the measurement noninvariance issue. One challenge, however, is to correctly model action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The Conway Maxwell Poisson Model (CMPCM;Forthmann et al, 2020) has no discrimination parameters like a Rasch model, while the Two Parameter Conway Maxwell Poisson Model (2PCMPCM; Beisemann, 2022) includes discrimination parameters. Qiao, Jiao, and He (2023) propose a CMP-based joint modeling approach. Tutz (2022) provides an alternative approach all together for dispersion handling.…”
Section: Every Trait Counts: Marginal Maximum Likelihood Estimation F...mentioning
confidence: 99%
“…The Conway Maxwell Poisson Model (CMPCM;Forthmann et al, 2020) has no discrimination parameters like a Rasch model, while the Two Parameter Conway Maxwell Poisson Model (2PCMPCM; Beisemann, 2022) includes discrimination parameters. Qiao, Jiao, and He (2023) propose a CMP-based joint modeling approach. Tutz (2022) provides an alternative approach all together for dispersion handling.…”
Section: Every Trait Counts: Marginal Maximum Likelihood Estimation F...mentioning
confidence: 99%
“…Other studies have addressed joint modelling by including not only the number of actions but also even more complicated features, such as action sequences, time, response, and background variables (Han et al, 2019;Tang et al, 2020;Ulitzsch et al, 2021). Qiao et al, (2022) conducted a multigroup joint model with the response, response time, and action sequence, which focused on the group invariance of gender. However, rare studies yet showed the framework of cross-country comparison of latent variables measured by the processing indicators together with the measurement invariance examination for processing data in an international large-scale survey.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the utility of process data for a multitude of practical tasks: To start, process data can provide additional information on the measured proficiency or skills, allowing better measurement via process-incorporated scoring rules (Zhang et al, 2023) and process-based measurement models, which typically associate continuous latent proficiency (Chen, 2020; Han et al, 2022; LaMar, 2018; Liu et al, 2018; Xiao & Liu, 2024) or discrete latent skill mastery (Zhan & Qiao, 2022; Liang et al, 2022) with examinees’ choices of correct/incorrect subsequent actions, observed action subsequences, or sequence length. Furthermore, analyses of behavioral characteristics associated with successful/unsuccessful final performance (e.g., Gao, Cui, et al, 2022; Gao, Zhai, et al, 2022; Greiff et al, 2015; He & von Davier, 2016; Qiao & Jiao, 2018; Qiao et al, 2023; Ulitzsch et al, 2021, 2023) can inform test validation and automated scoring. Exploratory analyses of action sequences or sequence-derived patterns, often with cluster analysis (Eichmann et al, 2020; He et al, 2019; Gao, Cui, et al, 2022; Gao, Zhai, et al, 2022; He, Borgonovi, & Suárez-Álvarez, 2023; Hao & Mislevy, 2019; Ulitzsch et al, 2022) or with topic modeling of actions or subsequences (Fang & Ying, 2020; Xu et al, 2018), have revealed different behavioral prototypes among the examinees as they face the same task, providing insights on how individuals navigate and approach computerized tests, digital platforms encountered in daily life, collaborative problems, etc.…”
mentioning
confidence: 99%